From cash to private and public digital currencies. The risk of financial instability and “modern monetary Middle ages” - Belke, Ansgar; Beretta, Edoardo (Economics and Business Letters, 2020)
The article analyzes the unstable equilibrium between further developing national monetary systems by means of (private/public) digital currencies while maintaining financial stability as secured by “tangible” store of values like notes/coins. Which are those elements of innovation improving today’s payments system? And, at the same time, which modern trends might destabilize the above-mentioned equilibrium? The paper will identify fundamental monetary principles to be respected, no matter what the innovation level in post-modern economies might soon look like. Cryptocurrencies will be also compared to central bank digital currencies (CBDC), which might soon complement or even replace notes and coins. But, is cash truly a “barbarous relic”? And, which impact might have its legal limitation (as occurring in several European countries)?